Ventilation Strategies during Neonatal Cardiopulmonary Resuscitation - Baik, Nariae; O’Reilly, Megan; Fray, Caroline; van Os, Sylvia; Cheung, Po-Yin; Schmölzer, Georg M. (Frontiers in Pediatrics, 2018)
Approximately, 10-20% of newborns require breathing assistance at birth, which remains the cornerstone of neonatal resuscitation. Fortunately, the need for chest compression (CC) or medications in the delivery room (DR) is rare. About 0.1% of term infants and up to 15% of preterm infants receive these interventions, this will result in approximately 1 million newborn deaths annually worldwide. In addition, CC or medications (epinephrine) is more frequent in the preterm population (~15%) due to birth asphyxia. A recent study reported that only 6 per 10,000 infants received epinephrine in the delivery room. Further, the study reported that infants receiving epinephrine during resuscitation had a high incidence of mortality (41%) and short-term neurologic morbidity (57% hypoxic-ischemic encephalopathy and seizures). A recent review of newborns who received prolonged CC and epinephrine but had no signs of life at 10 minutes following birth noted 83% mortality, with 93% of survivors suffering moderate-to-severe disability. The poor prognosis associated with receiving CC alone or with medications in the DR raises questions as to whether improved cardiopulmonary resuscitation (CPR) methods specifically tailored to the newborn could improve outcomes.